Udep Saree and Matee syahid: Local Ethical Reasoning in Acehnese Anti-Colonial Resistance - Muhammad Maulana; Iskandar; Muhammad Hendri; Gustira Monita (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2026)
This article examines udep saree, matee syahid; an Acehnese hadih maja expression translated here as "shared dignified life and martyr's death" as a local ethical vocabulary through which anti-colonial resistance in Aceh can be interpreted. Although the expression functions as a single proverbial unit, this study analyzes its two constituent ethical orientations in relational terms, arguing that their meanings are mutually constitutive rather than independent. Drawing on qualitative document analysis, the study engages a corpus that includes hadih maja collections, Acehnese cultural materials, historical accounts, colonial and postcolonial scholarship, news-based memory sources, filmic representations, and memorial inscriptions. The findings demonstrate that udep saree articulates an ethical orientation toward dignity, solidarity, reciprocity, and religious responsibility in communal life, while matee syahid designates a limit condition in which those same values, ie., religious commitment, dignity, and communal obligation, are sustained through sacrificial readiness under colonial domination. Together, the two expressions constitute a shared moral horizon through which resistance was rendered ethically intelligible within Acehnese local moral worlds. This article contributes to heritage studies and postcolonial ethics by demonstrating how proverbial traditions function as repositories of ethical reasoning and how attending to such traditions complicates reductive accounts of resistance as pathology, religious fanaticism, or violence alone.